Efektivitas Ekstrak Biji Mahkota Dewa (Phaleria papuena Warb) Dalam Mengendalikan Hama Spodoptera exigua Hubner (Lepidoptera: Noctuidae) Pada Pertanaman Bawang Merah - Shahabuddin Shahabuddin; Nur Khasanah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
A study aiming at comparing the effectiveness of seed extract of Phaleria papuena Warb and chemical insecticides for controlling beet armyworm pest (Spodoptera exigua Hubner) at the onion crops has been conducted. The experiment was set up by using a completely randomized design (CRD) with five treatments and tree replicates. The treatments applied were: without insecticide application as a control (P0), botanical insecticide, Phaleria papuena extract 2% (P1), 4% (P2), and 6% (P3), and chemical insecticide, prevathon 50 SC (P4). Variables measured were Spodoptera exigua population density and intensity of pest infestation. Results showed that application of botanical  and chemical insecticides significantly reducing the population density and the infestation of Spodoptera exigua. Effectiveness of Phaleria papuena extract 6% (P3) and prevathon (P4) was not significantly different in controlling Spodoptera exigua. In average, the application of Phaleria. papuena extract 6% (P3) and prevathon (P4) reduced population density at 9.4% and 9.3%, respectively, and infestation intensity of Spodoptera exigua 37.8% and 36.7%, respectively. These results suggest that the seed extract of Phaleria papuena is highly potential to be developed as botanical insecticide. Key Words : Botanical insecticides, Phaleria papuena, Spodoptera exigua.